The level of anxiety in healthcare workers and their children during the COVID-19 pandemic - GÖKSU, MUHSİNE; ERDOĞDU, AYŞE BURCU (My University, 2023)
During the early stages of the COVID-19 pandemic, healthcare workers (HcWs) reported having high levels of psychological stress caused by the risk of being infected and infecting their families, social isolation, and inadequate protective equipment. This study aimed to determine the level of anxiety and related factors in HcWs and their children during the first phase of the COVID-19 pandemic in Turkey. Online questionnaires were sent to HcWs with children aged 8–18 years via e-mail and WhatsApp messages. In total, 144 HcWs and 135 of their children participated in this study. HcWs completed the State-Trait Anxiety Inventory state subscale (STAI-S) and the COVID-19 Risk Perception Scale. Their children completed the Screen for Child Anxiety-Related Emotional Disorders (SCARED). STAI-S and COVID-19 Risk Perception Scale scores of the HcWs in direct contact with COVID-19 patients were significantly higher than of those not in direct contact. Moreover, the children of HcWs that were in direct contact with COVID-19 patients had significantly higher SCARED subscale scores than those whose parents were not in direct contact. There was a significant correlation between the SCARED somatic/panic subscale scores and HcW STAI-S scores. The presence of a mental illness and direct contact with COVID-19 patients were the 2 main predictors of COVID-19 risk perception and the level of anxiety in HcWs. During the COVID-19 pandemic the children of HcWs were observed to be a mentally sensitive group, and preventive mental health programs should be developed.
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Sağlık Bilimleri; Social Sciences and Humanities; Psychology; Health Sciences; Klinik Tıp (MED); Temel Bilimler (SCI); Psikiyatri; PSİKOLOJİ, BİYOLOJİK; Clinical Medicine (MED); Natural Sciences (SCI); PSYCHIATRY; PSYCHOLOGY; PSYCHOLOGY, BIOLOGICAL; Psikiyatri ve Ruh Sağlığı; Biyolojik Psikiyatri; Yaşam Bilimleri; Psychiatry and Mental Health; Biological Psychiatry; Life Sciences; Anxiety; Children; COVID-19; Healthcare workers